Learning Challenges and Mastery Level of Grade 8 Learners in Physical Education and Health Under the Revised K–10 Curriculum: Basis for An Innovative Learning Intervention - Joshua A. Bolante; Nikki Crystel A. Elic (INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH AND ANALYSIS, 2026)
This study examined the learning challenges and mastery level of Grade 8 learners in Physical Education and Health (PEH) under the Revised K–10 Curriculum and served as the basis for proposing innovative learning interventions. Unlike previous studies that primarily focused on either academic performance or isolated learning factors, this study provided a comprehensive assessment by examining multiple dimensions of learning challenges including learning competencies, instructional strategies, facilities and equipment, assessment methods, and motivation and participation and their relationship with learners’ mastery across the cognitive, affective, and psycho motor domains within the context of the Revised K–10 Curriculum. Specifically, it determined the learners' profile, the level of learning challenges encountered, and their mastery level in the three learning domains. The study employed a quantitative descriptive-correlational research design involving 132 Grade 8 learners from Casimiro A. Ynares Sr. Memorial National High School for School Year 2025–2026 who were selected through purposive criterion-based sampling. Data were gathered using previous academic records and a validated researcher-made questionnaire and were analyzed using frequency, percentage, weighted mean, t-test, one-way ANOVA, and Pearson product-moment correlation. The findings revealed that learners experienced a high level of learning challenges but demonstrated high mastery across the three learning domains. Significant differences were found in both learning challenges and mastery level when grouped according to profile variables, and a strong significant relationship existed between learning challenges and mastery level. A distinctive contribution of this study is the development of an Innovative Learning Intervention Framework for Enhancing Student Outcomes and Strengthening Instructional Practices in Physical Education and Health, which integrates the identified learning challenges with evidence-based instructional strategies to improve learner engagement, participation, and mastery under the Revised K–10 Curriculum.